Reduction of needlestick injuries in healthcare personnel at a university hospital using safety devices - Hoffmann, Cornelia; Buchholz, Lutz; Schnitzler, Paul (Journal of occupational medicine and toxicology, 2013)
Healthcare personnel (HCP) is exposed to bloodborne pathogens through occupational risk factors. The objective of this study was to compare the incidence of needlestick injuries (NSIs) before and after the introduction of safety devices in all departments of our hospital.